Non‐canonical endogenous expression of voltage‐gated sodium channel NaV1.7 subtype by the TE671 rhabdomyosarcoma cell line. (27th April 2022) - Ngum, Neville M.; Aziz, Muhammad Y. A.; Mohammed Latif, Liaque; Wall, Richard J.; Duce, Ian R.; Mellor, Ian R.
Abstract : Abstract: The human TE671 cell line was originally used as a model of medulloblastoma but has since been reassigned as rhabdomyosarcoma. Despite the characterised endogenous expression of voltage‐sensitive sodium currents in these cells, the specific voltage‐gated sodium channel (VGSC) subtype underlying these currents remains unknown. To profile the VGSC subtype in undifferentiated TE671 cells, endpoint and quantitative reverse transcription–PCR (qRT‐PCR), western blot and whole‐cell patch clamp electrophysiology were performed. qRT‐PCR profiling revealed that expression of the SCN9A gene was ∼215‐fold greater than the SCN4A gene and over 400‐fold greater than any of the other VGSC genes, while western blot confirmed that the dominant SCN9A RNA was translated to a protein with a molecular mass of ∼250 kDa. Elicited sodium currents had a mean amplitude of 2.6 ± 0.7 nA with activation and fast inactivation V 50 values of −31.9 ± 1.1 and −69.6 ± 1.0 mV, respectively. The currents were completely and reversibly blocked by tetrodotoxin at concentrations greater than 100 nm (IC50 = 22.3 nm ). They were also very susceptible to the NaV 1.7 specific blockers Huwentoxin‐IV and Protoxin‐II with IC50 values of 14.6 nm and 0.8 nm, respectively, characteristic of those previously determined for NaV 1.7. Combined, the results revealed the non‐canonical and highly dominant expression of NaV 1.7 in the human TE671 rhabdomyosarcoma cell line. We show that the TE671 cell line is an easy to maintain and cost‐effective model for the study of NaV 1.7, a major target for the development of analgesic drugs and more generally for the study of pain. Key points: Undifferentiated TE671 cells produce a voltage‐sensitive sodium current when depolarised. The voltage‐gated sodium channel isoform expressed in undifferentiated TE671 cells was previously unknown. Through qRT‐PCR, western blot and toxin pharmacology, it is shown that undifferentiated TE671 cells dominantly (>99.5%) express the NaV 1.7 isoform that is strongly associated with pain. The TE671 cell line is, therefore, a very easy to maintain and cost‐effective model to study NaV 1.7‐targeting drugs. Abstract : Abstract figure legend Phase contrast image of undifferentiated TE671 cells and the experimental approaches used to confirm dominant expression of the NaV 1.7 subtype of voltage‐gated sodium channels. These included PCR, western blotting and patch‐clamp electrophysiology with NaV 1.7‐specific toxins such as Protoxin‐II from the tarantula spider, Thrixopelma pruriens .